2014
DOI: 10.1007/s11764-013-0336-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress among adult survivors of childhood cancer

Abstract: Purpose To estimate the prevalence of emotional distress in a large cohort of adult survivors of childhood cancer and evaluate the interrelationship of risk factors including cancer-related late effects. Methods 1,863 adult survivors of childhood cancer, median age of 32 years at follow-up, completed comprehensive medical evaluations. Clinically relevant emotional distress was assessed using the Brief Symptom Inventory-18 and was defined as T-scores ≥63. Odds ratios (OR) and 95% confidence intervals (CI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 63 publications
3
39
0
Order By: Relevance
“…Regarding diagnostic groups, 17 studies included patients with heterogeneous diagnoses . Furthermore, nine studies focused on specific homogenous subgroups of patients with diagnoses such as acute lymphoblastic leukaemia (ALL), leukaemia, lymphoma, Hodgkin's lymphoma, rhabdomyosarcoma, osteosarcoma, soft tissue sarcoma, Ewing's sarcoma, other bone tumours and CNS tumours …”
Section: Resultsmentioning
confidence: 99%
“…Regarding diagnostic groups, 17 studies included patients with heterogeneous diagnoses . Furthermore, nine studies focused on specific homogenous subgroups of patients with diagnoses such as acute lymphoblastic leukaemia (ALL), leukaemia, lymphoma, Hodgkin's lymphoma, rhabdomyosarcoma, osteosarcoma, soft tissue sarcoma, Ewing's sarcoma, other bone tumours and CNS tumours …”
Section: Resultsmentioning
confidence: 99%
“…In a longitudinal study of cancer survivors in the USA between 1998 and 2000, Hewitt et al [1] found no racial differences in the likelihood of reporting psychosocial problems among individuals with a history of cancer. Similarly, Oancea et al [14] observed no racial differences in emotional distress levels among adult survivors of childhood cancer. In another study, Nelson et al [15] observed similar levels of distress and anxiety between African American prostate cancer patients and a matched Caucasian sample.…”
Section: Introductionmentioning
confidence: 93%
“…Adults who suffered from cancer in childhood are less likely to take up any form of physical activity and are more prone to lead an inactive lifestyle [18]. oancea et al [19] assessed the rate of emotional disorders among a group of adults who had suffered from cancer in childhood. The results show that those people experience a chronic feeling of anxiety: they associate childhood solely with pain and problems with memory and learning.…”
Section: Discussionmentioning
confidence: 99%